تأثير استعمالات الأرض على حركة النقل و المرور في مدينة صرمان للفترة من 1980 – 2024 (Comprehensive Journal of Science, 2025)
There is significant interest in land use planning, which forms the basis for organizing and planning cities and achieving optimal use of urban land. However, Libyan cities have not received the necessary attention in studying land use and transportation, despite the importance of these uses to citizens.Throughout its history, the study area has witnessed a marked increase in all areas, such as population growth, the number and size of transportation modes, the multiplicity of activities and uses, and the complexity of life. These developments have had a clear impact on the city's structure, particularly in the functions of transportation and traffic. This development has resulted in a mixture of uses, leading to the emergence of numerous problems, particularly those related to transportation and traffic. The streets now experience numerous traffic jams, congestion, and environmental and noise pollution.The research arrives at several conclusions, the most important of which are the deterioration of the road network and the narrowness of sidewalks on many streets. There is poor planning of road intersections, a shortage and absence of parking spaces, a lack of pedestrian or bicycle lanes, and the inability of the street network to accommodate the large traffic congestion resulting from the increase in vehicle numbers. The study recommends adopting a scientific and planning approach to developing the city's road network to suit current and future traffic volume.